This one confused me since it revolved around what seemed like dividing trig function by another function

Write the following expression in terms of the tangent function
2 / ((cos(r^2 - s^2) / (sin(r^2 - s^2))

= ?

I know tan t = sin t / cos t. So would I multiply by the reciprocal? Or since cos / sin = cot would I put the 2 over cotangent. this one confused me

1 answer

2 / ((cos(r^2 - s^2) / (sin(r^2 - s^2))
= 2 * (sin(r^2 - s^2) / (cos(r^2 - s^2)
= 2 tan (r^2 - s^2)
Similar Questions
    1. answers icon 1 answer
    1. answers icon 1 answer
  1. i have some problems doing trigthe first one is: Show that cos(x/2) sin(3x/2) = ½(sinx + sin2x) i know that you are supposed to
    1. answers icon 0 answers
  2. How would you solve this trig function:cos2x=sin^2-2 how do you know what trig identities to use?
    1. answers icon 4 answers
more similar questions